Calculation of the external factors influence indices on plants and its application to Deschampsia antarctica Ė. Desv. populations - Miryuta, N.; Wojciechowski, K.; Parnikoza, I. (Ukrainian Antarctic Journal, 2019)
The main objective of the research is developing and describing in detail the calculation algorithm of the United Temperature Influence Index (UTII) and United Macroelements content in Soil Influence Index (UMCSII) on basic plant characteristics in sample populations. Additionaly, we present an example of its application in Deschampsia antarctica È Desv. research at Galindez Island, Argentine Islands, maritime Antarctic under natural condition based on experimental data sets. The final goal of the research was to evaluate the UTII and UMCSII, based on the sample plant populations contribution to the United Quality Latent Index of adaptability (UQLI). Methods. The surface temperature data set was obtained by temperature loggers at each individual plant population during April 2017 — April 2018. To determine the individual D. antarctica cover and measure the morphometric parameters of eleven D. antarctica populations, we evaluated leaf length, inflorescence length, flower length (by lower flower glume), and the number of flowers in inflorescence. Protein densitometry profiles of seeds for eleven D. antarctica populations were analyzed. To obtain the United Temperature Influence Index (UTII) and United Macroelements Content in Soil Influence Index (UMCSII) on basic plant characteristics, the extreme grouping method was applied. This method is described in current work in detail. The estimation of UTII and UMCSII were calculated by pairwise comparisons of spatial pair differences indices sets. Results. The calculation algorithms of the United Temperature Influence Index (UTII) and United Macroelements Сontent in Soil Influence Index (UMCSII), based on the example of eleven populations of D. antarctica, were developed and described in detail for Galindez Island in the 2017/18 season. Determining the total contribution of UTII and UMCSII to the UQLI is an example of comparing the value of temperature and soil macroelements to environmental parameters. Conclusions. UTII was shown to have a significant contribution to the UQLI in December and January, when the largest spatial temperature variations were observed. UMCSII did not have a statistical confidence of contribution to the UQLI, but sum with the UTII increased UTII contribution value to the UQLI. The index UTII is proposed to describe an influence of source temperature data to a large number of plant populations sample different characteristics by reducing the dimension to one number. The index UMCSII is proposed to describe an influence of a large number of source macroelements content in soil data to sample populations covers by reducing the dimension to one number. The UTII and UМCSII sets can be used to compare them with sets of the UQLI of adaptability populations sample of the same species growing under different conditions to construct correlation models for different populations.